Water Quality Index Analysis for Water Drinking and Irrigation in the Sumowono Groundwater Basin - Thomas Triadi Putranto; Novie Susanto; Dina Rahayuning Pangestuti; Aji Bagas Putro (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
The Sumowono Groundwater Basin is a cross-district basin located in Central Java Province, between Temanggung Regency, Kendal Regency, and Semarang Regency. The people in this area obtain fresh water from either dug wells or springs. The purpose of this research is to determine the feasibility of groundwater for drinking water and irrigation purposes. The method used was hydrogeological mapping and physical and chemical analysis of 10 groundwater samples. The samples were subjected to empirical testing of the Groundwater Quality Index to determine the feasibility of drinking water and irrigation using Sodium Adsorption Ratio (SAR) analysis and Wilcox diagram. The results showed that all samples physically have tasteless and odorous properties. For the chemical properties produced in the ten samples, the pH value ranges from about 6.85 - 7.27. The electrical conductivity is between 71.6 - 511 µS/cm. Total Dissolved Solids values are between 45.82 and 327.04 mg/L, with total hardness values ranging from 10 to 170 mg/L. From the results of the SAR analysis, it is found that the groundwater classes were included in S1C1 and S1C2, so that groundwater has low alkaline in both sodium and salinity, respectively. Thus, groundwater is considered suitable for consumption and irrigation purposes,